Knee-ankle-foot orthosis with powered knee for support in the elderly - Pott, Peter Paul; Wolf, Sebastian Immanuel; Block, Julia; Drongelen, Stefan van; Heitzmann, Daniel; Rettig, Oliver (Proceedings of the Institution of Mechanical Engineers. Part H, Journal of engineering in medicine, 2017)
A prototype of a powered knee orthotic device was developed to determine whether fractional external torque and power support to the knee relieves the biomechanical loads and reduces the muscular demand for a subject performing sit-to-stand movements. With this demonstrator, consisting of the subsystems actuation, kinematics, sensors, and control, all relevant sensor data can be acquired and full control is maintained over actuator parameters. A series-elastic actuator based on a direct current motor provides up to 30 Nm torque to the knee via a hinge joint with an additional sliding degree of freedom. For reasons of feasibility under everyday conditions, user intention is monitored by employing a noninvasive, nonsticking muscle activity sensor to replace electromyographic sensors, which require skin preparation. Furthermore, foot plates with force sensors have been developed and included to derive ground reaction forces. The actual knee torque needed to provide the desired support is based on an inverse dynamics model using ground reaction forces signals and leg kinematics. A control algorithm including disturbance feed forward has been implemented. A demonstration experiment with two subjects showed that 23 % of moment support in fact leads to a similar reduction in activation of the main knee extensor muscle.